The Element of Plot and Setting of Raya and The Last Dragon - Purnama Yasa, I Wayan Andi; Mulyawan, I Wayan; Ida Setianingsih, Ni Ketut Alit (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 30 No 1 (2023): Maret, 2023)
A story's plot is the series of events that make up the story. Plot entertains readers to turn the pages of a literary work. Setting refers to the time and space in which the events of the plot happen. It means that in analysing the setting, one should analyse the main event in the plot arranged in a story. Sometimes discussing the plot and setting there is still in the analysis that needs to be explained more deeply and incomplete according to the story in the movie. This study aimed to identify the plot’s elements and analyse in detail the setting in every sequence in Raya And The Last Dragon movie. The theories applied DiYanni (2004)'s theory of plot and Kenny's theory (1966) of setting were both used in this study. Data of this study was taken from observation and taking note of the movie, and script of the movie, the method applied was a qualitative method. The collected data were selected and put into plot and type of setting categories, which were descriptively analysed based on the theory applied. The results of this study show that the plots of this movie consist of five parts, namely exposition, complication, turning point or climax, falling action, and is ended by a resolution (denouement). The setting of this story can be analysed in terms of the type of setting which includes a neutral setting and a spiritual setting.